Primary bone lymphoma of the ilium successfully treated without radiation. Issue 12 (23rd September 2020) - Nguyen, Charles B.; Li, Monica; Verstovsek, Gordana; Sen, Urmi; Swierenga, Christi; Huang, Quillan; Rivero, Gustavo; Yellapragada, Sarvari V.
Abstract: The addition of radiation therapy to chemotherapy and impact on outcomes in primary bone lymphoma is not clear. Nonetheless, tumor location must be considered as radiation to marrow‐rich bone areas can lead to myelosuppression and myelotoxicity. Abstract : The addition of radiation therapy to chemotherapy and impact on outcomes in primary bone lymphoma is not clear. Nonetheless, tumor location must be considered as radiation to marrow‐rich bone areas can lead to myelosuppression and myelotoxicity.